Simulating surgical skills in animals: systematic review, costs & acceptance analyses - Bergmeister, Konstantin D.; Aman, Martin; Kramer, Anne; Schenck, Thilo L.; Riedl, Otto; Däschler, Simeon C.; Aszmann, Oskar C.; Bergmeister, Helga; Golriz, Mohammad; Mehrabi, Arianeb; Hundeshagen, Gabriel; Enkhbaatar, Perenlei; et al. (Frontiers in veterinary science, 2020)
Background: Modern surgery demands high-quality and reproducibility. Due to new working directives, resident duty hours have been restricted and evidence exists that pure on-the-job training provides insufficient exposure. We hypothesize that supplemental simulations in animal models provide a realistic training to augment clinical experiences. This study reviews surgical training models, their costs and survey results illustrating academic acceptance. Methods: Animal models were identified by literature research. Costs were analyzed from multiple German and Austrian training programs. A survey on their acceptance was conducted among faculty and medical students. Results: 915 articles were analyzed, thereof 91 studies described in-vivo animal training models, predominantly for laparoscopy (30%) and microsurgery (24%). Cost-analysis revealed single-training costs between 307€ and 5861€ depending on model and discipline. Survey results illustrated that 69% of the participants had no experience, but 66% would attend training under experienced supervision. Perceived public acceptance was rated intermediate by medical staff and students (4.26; 1 - low, 10 high). Conclusion: Training in animals is well-established and was rated worth attending in a majority of a representative cohort to acquire key surgical skills, in light of reduced clinical exposure. Animal models may therefore supplement the training of tomorrow’s surgeons to overcome limited hands-on experience until virtual simulations can provide such educational tools.